Life cycle assessment of pulp-moulded and thermoformed oil palm fibre-based food tray - Campbell Skinner; M. Jawaid; Balbir Singh; Amir Alzahri; Rob Elias; Hassan Fouad; M. Hashem (Discover Applied Sciences)
Abstract This study used life cycle assessment to assess carbon emissions associated with the production of three novel bio-based food punnets and to compare them with an equivalent made from polypropylene (PP). Two of the punnet formats included empty fruit bunch fibre (EFB), an abundant source waste biomass originating from the palm oil industry. Two production technologies were assessed, with one of the punnets being pulp-moulded (100% EFB fibre) and the others being thermoformed blends. Primary data for pulp-moulding was collected at factory-scale in Malaysia, while a novel fibre pretreatment step, necessary as a precursor to pulp-moulding this form of fibre, was only available at small-scale. The results showed that both the thermoformed punnets have lower GWPs than the PP equivalent, the best being that containing 18% EFB fibre, which had a 21% lower carbon footprint by weight, at the factory gate. Results for the pulp-moulded format were less clear due to the small-scale of operation during pretreatment. Results for the pre-treatment step are therefore high as presented, however analysis suggests that where efficiencies-of-scale can achieve a 57% reduction in emissions associated with this step, then pulp-moulded punnets will have lower GWPs than the thermoformed samples. The key future question from this preliminary assessment is therefore the extent to which the EFB fibre pretreatment step can be optimised in the pulp-moulded production scenario. Further development and scaling-up of the novel pretreatment process would now be beneficial, however all three punnet formats have potential to reduce emissions relative to those of fossil-based plastic equivalents.